Genetic diversity of local rice varieties (Oryza sativa L.) in Vietnam’s Mekong Delta based on SSR markers and morphological characteristics - Tran Huu Phuc; Van Quoc Giang; Nguyen Van Manh; Huynh Ky (Indonesian Journal of Biotechnology, 2021)
Based on target traits, use of the genetic diversity of rice is beneficial for crop improvement. In this study, 41 rice varieties local to Vietnam’s Mekong Delta were evaluated on the basis of 11 quantitative morphological traits, along with the assessment of genetic diversity according to 50 SSR markers. The actual yield had a significance level of 0.05, while plant height and panicles per square meter had a high significance level of 0.001. Cluster analysis based on 11 quantitative traits also revealed that two were the optimal number of clusters used in this study. The highest polymorphic information content (PIC) value obtained was for RM286 (0.49), with a range of 0.00 to 0.49 and an average PIC of 0.14. Both structure and phylogenetic tree analyses as inferred from 50 SSR markers by the unweighted pair‐group method with arithmetic mean (UPGMA) also indicated that the 41 local rice varieties could be divided into two major groups. This study provides a useful information for Mot bui do cao CM, and Mot bui five varieties for improvements in the yield and intermediate amylose content of local rice‐breeding programs in future, especially for the Mekong Delta region.